(untitled) (Hekima Review, 2023)
Change is necessary in order to remain alive. This is true on all levels, for individuals and communities, for physical and spiritual life. The Old Testament testifies to the latter. It shows actualization to correspond better to a new time and way of thinking. It reports official reform, to follow more accurately the prescriptions of the Torah. It reveals difficulties with religious leaders who do not comply with what is expected from them. It indicates ways to spiritual renewal, going far beyond traditional concepts of piety. It pleads for conversion throughout. Overall, being re-formed appears as a divine gift.